APAKAH RISK TAKING PROPENSITY DAN INTERNAL LOCUS OF CONTROL MEMILIKI HUBUNGAN DENGAN INTENSI BERWIRAUSAHA PADA SISWA KELAS XII SMK NEGERI 1 SRAGEN? - Rofifah Aisyah Luthfi; Sohidin Sohidin (Universitas Sebelas Maret, 2024)
ABSTRACTThis study aims to obtain empirical evidence: (1) the relationship between risk-taking courage with entrepreneurial intentions in students; (2) the relationship between internal locus of control with entrepreneurial intentions in students; (3) the relationship between risk-taking courage and internal locus of control with entrepreneurial intentions in students. The research method used is descriptive quantitative method correlational approach. The population in this study were XII grade students of SMK Negeri 1 Sragen totaling 557 students. Then the sample of 232 students using proportional random sampling technique. The results of this study are (1) there is a positive and significant relationship between the courage to take risks with entrepreneurial intentions in class XII students of SMK Negeri 1 Sragen with a significance value of 0.000 <0.005; (2) there is a positive and significant relationship between internal locus of control with entrepreneurial intentions in class XII students of SMK Negeri 1 Sragen with a significance value of 0.000 < 0.005; (3) there is a positive and significant relationship between courage to take risks and internal locus of control with entrepreneurial intentions of class XII students of SMK Negeri 1 Sragen with a significance value of 0.000 < 0.005. Based on the results of the study, researchers recommend further study by adding other variables, such as emotional intelligence variables, so as to produce research that is more complex than previous studies.Keywords: Risk taking propensity, Internal locus of control, and Entrepreneurial Intention.ABSTRAKPenelitian ini bertujuan untuk memperoleh bukti empirik: (1) hubungan antara risk taking propensity dengan intensi berwirausaha pada siswa; (2) hubungan antara internal locus of control dengan intensi berwirausaha pada siswa; (3) hubungan antara risk taking propensity dan internal locus of control dengan intensi berwirausaha pada siswa. Metode penelitian yang digunakan adalah metode kuantitatif deskripstif pendekatan korelasional. Populasi dalam penelitian ini adalah siswa kelas XII SMK Negeri 1 Sragen sejumlah 557 siswa. Kemudian sampel sejumlah 232 siswa yang menggunakan teknik proportional random sampling. Hasil dari penelitian ini adalah (1) terdapat hubungan yang positif dan signifikan antara risk taking propensity dengan intensi berwirausaha pada siswa kelas XII SMK Negeri 1 Sragen dengan nilai signifikansi 0,000 < 0,005; (2) terdapat hubungan yang positif dan signifikan antara internal locus of control dengan intensi berwirausaha pada siswa kelas XII SMK Negeri 1 Sragen dengan nilai signifikansi 0,000 < 0,005; (3) terdapat hubungan yang positif dan signifikan antara risk taking propensity dan internal locus of control dengan intensi berwirausaha siswa kelas XII SMK Negeri 1 Sragen dengan nilai signifikansi 0,000 < 0,005. Berdasarkan hasil penelitian tersebut, peneliti merekomendasikan untuk mengkaji lebih lanjut dengan menambah variabel lain, misalnya variabel kecerdasan emosional, sehingga dapat menghasilkan penelitian yang lebih kompleks dari penelitian sebelumnya.Kata Kunci: Risk taking propensity, Internal locus of control, dan Intensi Berwirausaha